FAKTOR-FAKTOR PENGARUH KESADARAN BERASURANSI DI KOTA DENPASAR - Nyoman Djinar Setiawina, Shri Rangga Murthi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
There is a causal relationship between economic growth and insurance growth. Theoretical study shows that the high demand for insurance in an area is a representation of the high awareness of insurance in the area. The purpose of this study was to analyze the effect of age, gender, education level, and income on insurance awareness in Denpasar City partially and simultaneously. The population and sample used in this study used the Slovin formula. The method of determining the sample using proportional stratified random sampling. The analysis technique used in this study is multiple linear regression test. The variables of age, gender, education level and income simultaneously influence insurance awareness. Age is partially positive and significant effect on insurance awareness. Gender partially influences insurance awareness. The level of education partially has a positive and significant effect on insurance awareness. Income partially has a positive and significant effect on insurance awareness.